RFID -GSM Based Vehicle Authentication System - Bhaskar, Pranay S.; Sakhare, Pushpak R.; Gaikwad, Ruchita A. (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Now a days, especially in India, we face the problem of traffic, & a huge rush, because the use of increase in automobiles and in which many of the automobiles or vehicles are not registered with their insurance, license etc . And because of this , traffic police officers have to stop and check public’s legal documents regarding their vehicles and because of this the time of public or the traffic controller gets waste. To avoid this irresponsible behavior of the public, we are trying to implement a device called RFIDGSM based vehicle authentication system.